Farmer Motivation in Implementing Good Diary Farming Practice (GDFP): Case Study on Lembu Lestari Group in Tulungrejo Village - Huda, Ainun; Likah, Sad; Siswoyo, Siswoyo (University of Jember, 2024)
Poor implementation of Good Dairy Farming Practices (GDFP) has an impact on the low quantity and quality of milk. The FMD pandemic that attacked further aggravated the condition. Efforts to recover the impact of FMD need strong motivation from farmers to tighten the implementation of GDFP. Dairy farming has been part of the lives of the people of Tulungrejo Village for a long time. Encouragement that can motivate farmers to survive and rise from the impact of the outbreak needs to be known so that appropriate treatment can be carried out in accompanying farmers. The purpose of this study is to know the characteristics of farmers and describe the motivation of farmers in implementing GDFP. The research method uses the survey method. The sampling technique used was purposive sampling and was obtained by 22 respondents of breeders who were members of the Lembu Lestari Group. Data analysis using quantitative descriptive methods. The results showed that farmers in the Lembu Lestari Group were dominated by productive age, elementary school education level, had family dependents between 2-3 people, had varied livestock experience, and had livestock between 4-8 heads. The level of motivation in implementing GDFP which is implemented by existance needs, relatedness needs, growth needs is in the high category with a percentage of 87.78%.